Research advances on silence information regulator 6 as a potential therapeutic target for bone regeneration and repair - PAN, Wenzheng; HE, Yong; HUANG, Yue (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2024)
Segmental bone defects and nonunion of fractures caused by trauma, infection, tumor or systemic diseases with limited osteogenesis and prolonged bone healing cycles are challenging issues in orthopedic clinical practice. Therefore, identifying regulatory factors for bone tissue regeneration and metabolism is crucial for accelerating bone repair and reconstructing defective areas. Silence information regulator 6 (SIRT6), functioning as a deacetylase and nucleotide transferase, is extensively involved in the regulation of differentiation, apoptosis, metabolism, and inflammation in bone cells including osteoblasts and osteoclasts, and is considered to be an important factor in regulating bone metabolism. SIRT6 forms a complex with B lymphocyte-induced maturation protein 1 (Blimp1), down-regulates the expression of the nuclear factor κB (NF-κB) pathway, and promotes the expression of the ERα-FasL axis signal to inhibit osteoclast formation and maturation differentiation, thereby hindering bone resorption and increasing bone mass. In addition, SIRT6 activates the Akt-mTOR pathway to regulate the autophagy level and osteogenesis of bone marrow mesenchymal stem cells, inhibits glycolysis and reactive oxygen production in osteoblasts, promotes osteoblast differentiation through the CREB/CCN1/COX2 pathway and the bone morphogenetic protein (BMP) signaling pathway, enhances bone formation, and accelerates bone regeneration and repair of skeletal tissue. This article provides an overview of the research progress on SIRT6 in the pathophysiology of bone regeneration, revealing its potential as a novel therapeutic target for bone tissue repair to alleviate the progression of skeletal pathological diseases.